Effect of Resveratrol in Expression of Caspase-7 and Retinal Ganglion Cells in a Rat Model With Traumatic Optic Neuropathy - Yunita1,2 Budu3 , Andi Muhammad Ichsan4 , Habibah S Muhiddin4 (Indian Journal of Forensic Medicine & Toxicology, 2021)
Objective: To analize the effect of resveratrol to the expression of caspase-7 and density of retinal ganglioncells in a rat model with Traumatic Optic Neuropathy (TON) compared to control.Methods: This is an experimental study using Wistar rats. Samples were divided into four groups. Onenormal control group, 1 TON control group and 2 TON resveratrol groups. TON induced by clamping theoptic nerve retrobulbar with Hartmann Mosquito 2,5 inch. Resveratrol was given 10 mg/Kg and 20 mg/Kgin two resveratrol groups. Enucleation was performed 1 day after to evaluate the expression of Caspase-7 byimmunohistochemistry and density of retinal ganglion cell by hematoxicilin eosin staining.Results: Caspase-7 expression was lowest in the resveratrol 20 mg/kg treatment group (4.00 ± 2.00)compared to resveratrol 10 mg/kg treatment group (6.00±2.23), TON control group(6.00 ± 6.78) and normalcontrol group(7.20 ± 2.58). Retinal ganglion cell density was highest in the resveratrol 10 mg/kg treatmentgroup (27.23±2.75) compared to resveratrol 20 mg/kg treatment group (24.89±5.83), normal controlgroup(24.19±2.39) and the lowest in TON control group (22.96±4.62). Based on the Pearson correlation test,it was found that there was no correlation between Caspase-7 expression and retinal ganglion cell density ina rat model with TON (p: 0.178; r = 0.314)Conclusions: Resveratrol administration shows effect in lowering apoptosis marker caspase-7 and preservingretinal ganglion cell in traumatic optic neuropathy.